If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 4) + 4 = 7(x + 4) + 3 Reorder the terms: -3(4 + x) + 4 = 7(x + 4) + 3 (4 * -3 + x * -3) + 4 = 7(x + 4) + 3 (-12 + -3x) + 4 = 7(x + 4) + 3 Reorder the terms: -12 + 4 + -3x = 7(x + 4) + 3 Combine like terms: -12 + 4 = -8 -8 + -3x = 7(x + 4) + 3 Reorder the terms: -8 + -3x = 7(4 + x) + 3 -8 + -3x = (4 * 7 + x * 7) + 3 -8 + -3x = (28 + 7x) + 3 Reorder the terms: -8 + -3x = 28 + 3 + 7x Combine like terms: 28 + 3 = 31 -8 + -3x = 31 + 7x Solving -8 + -3x = 31 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -8 + -3x + -7x = 31 + 7x + -7x Combine like terms: -3x + -7x = -10x -8 + -10x = 31 + 7x + -7x Combine like terms: 7x + -7x = 0 -8 + -10x = 31 + 0 -8 + -10x = 31 Add '8' to each side of the equation. -8 + 8 + -10x = 31 + 8 Combine like terms: -8 + 8 = 0 0 + -10x = 31 + 8 -10x = 31 + 8 Combine like terms: 31 + 8 = 39 -10x = 39 Divide each side by '-10'. x = -3.9 Simplifying x = -3.9
| 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 | | (2x-5)=15 | | -3(t-5)+7t=6t-5 | | 2=x/6.4 | | 6-14=6+(-8) | | (a^4+4a+-8)=0 | | 12x^2y+18xy-6x=0 | | f(x)=15x^4-15x^2 | | a^4+4a-8=0 | | 45=7-2b | | 1/4x0.04 | | 12/7=k//8 | | .50c+.40=190 | | -4=6+2x | | 1.7=k/8 | | Log(x)=-8 | | r-9.8=-2.4 | | 4s=s-3 | | 5y+ax=0 | | x/12=2/8 | | -4x+by=6 | | 8-8x-4=-37+3x-14 | | 2.1y+37.8=7.4y+6 | | -7v+1=-5v+1 | | a+5y=0 | | 4x^2-12=4 | | 6x^3-13x^2-28=0 |